Consideraciones en torno a la familia Xenoperidae Poche, 1925 (Trentatoda, Digenea Carus, 1863) - Caballero y C., Eduardo (1959)
In vol. XIV, p, 816 of the monograph, Trematodes of animals and man (14), SKRJABIN reviews the family Xenoperidae Poche, 1925, comprising a single genus and species. In our judgment, this taxonomic entity is currently non-existent, since DOLLFUS (4) showed Xenopera Nicoll, 1915 to be a synonym of Proctoeces Odhner, 1911, an aberrant genus in the family Fellodistomatidae Odhner, 1911. Proctoeces Odhner, 1911 was placed in the subfamily. Proctoecinae Skrjabin & Koval, 1957 (17) within the family Fellodistomatidae Odhner, 1911, without considering its synonym, together with Gauhatiana Gupta, 1953, Mesolecitha Linton, 1910, Symmetrovesicula Yamaguti, 1938, and Urorchis Ozaki, 1927. YAMAGUTI (18, p. 34-38) included Proctoeces in the subfamily Heterochiinae Dollfus, 1950, also in Fellodistomatidae, together with Mesolecitha Linton, 1910, and gave Xenopera Nicoll, 1915 as a synonym of Proctoeces he considered all the species of this genus valid. Nevertheless, as DOLLFUS considered Proctoeces Odhner, 1911 to be aberrant, the creation of the new subfamily Proctoecinae Skrjabin & Koval, 1957 was justified; but we believe that, instead, its authors should have substituted the new name for Xenoperidae Poche, 1925, thus placing the species of this genus correctly as a consequence of their removal from Fellodistomatidae. We propose a new name, Proctoecidae, for the family, derived from the type genus in accordance with Article 4 of the International Code of Zoological Nomenclature and with Article 25 of the Law of Priority. We believe the subfamily name Proctoecinae Skrjabin & Koval should be conserved, comprising the five genera, Proctoeces Odhner, 1911, Gaubatiancl Gupta, 1953, Mesolecitha Linton, 1910, Symmetrovesicula Yamaguti , 1938, and Uforchis Ozaki, 1927, an arrangement which shows well the natural and phylogenetic relationships of the group. The diagnosis of Proctoecidae nom. nov. as given here includes the characters of the five constituent genera, with their valid species, synonyms, and type species. Proctoeces macrovitellus Winter, 1954 is excluded from the genus Proctoeces Odhner, 1911 as suggested by FREEMAN and LLEWELLYN (5). Dr. H. A. Winter has in preparation a note on this species showing his current opinion on its position.